An optimal purchase and sale power model considering microgrids. (10th December 2013) - Lei, Xia; Yan, Wen‐jie; Peng, Peng; Ye, Tao
Summary An essential part of the smart grid development is to connect the main transmission grid with microgrids that consist of distributed generation resources. The integration of microgrids and the transmission grid not only can improve the reliability of the power system operation but also can increase the competition of the electricity market. The effective trading between microgrid agents and a distribution company (DisCo) is consistent with the direction of smart grid development. Developing effective strategy to optimally schedule energy trading between microgrid agents and the DisCo will bring benefits to all parties and promote further development of distributed clean energy. By analyzing the operation characteristics of the electricity market with the addition of microgrid agents as new market participants, this paper presents a bi‐level optimization model that aims to maximize the benefits of microgrid agents and a DisCo while considering transmission loss factors from various generators, duality role of the microgrid agents who can either buy electricity from the wholesale market at volatile prices or sell electricity into the market or to its local consumers. The model presented in this paper jointly optimizes the energy schedules of the microgrid agents and the DisCo and determines the bid/offer price at which the microgrid agent buys and sells electricity from/to the DisCo. At last, simulation results are provided to demonstrate the feasibility and application of the proposed two‐level optimization model. Copyright © 2013 John Wiley & Sons, Ltd.